Risk and Management Accounting : Best practice guidelines for enterprise-wide internal control procedures - Collier, Paul M.; Berry, Anthony J.; Burke, Gary T.; Chartered Institute of Management Accountants (Amsterdam ; London : CIMA, 2007)
This CIMA research report builds on a pilot study undertaken by the authors. The main focus of the research was how risk management methods impacted on budgeting.
Includes bibliographical references (p. 127-130) and index.
Keywords: Managerial accounting; Risk management; Business and Management